Statistical characteristics of wind erosion events in the erosion area of Northern China - Shen, Yaping; Zhang, Chunlai; Wang, Xuesong; Zou, Xueyong; Kang, Liqiang (Catena (Giessen), 2018)
A wind erosion event is the basic minimum unit of an aeolian process. To understand the characteristics of such events, we analyzed wind speed data from 1980 to 2015 from 151 meteorological stations in the area of northern China subject to wind erosion. We classified wind erosion events into 15 levels based on the maximum wind speed during each event, and analyzed wind speed distribution of these different levels of events. The wind speed in each event level showed a significant linear distribution, providing the basis for improving the calculation of wind erosion: Qj = Tj ∙ ∑i=1i=j[R(ui) ∙ F(ui)] (details in the article). This would help to improve the calculation accuracy based on wind level compared to values based on average wind speed. We found that low-level wind erosion events were frequent but shorter, whereas high-level events were less frequent, but lasted longer and contributed more to wind erosion. >87% of the total wind erosion events lasted no >10 h. Only 9% of the individual wind erosion events lasted 11 to 20 h. Fewer than 4% of individual events lasted >20 h. Thus, it is important to consider the roles of both weak wind erosion events (<11.0 m s−1) and strong wind erosion events (≥11.0 m s−1). The spatial distribution of wind erosion events varied greatly among the sub-areas in the wind erosion area of northern China, demonstrating environmental differences should be considered when studying the effects of wind erosion in the large study area. •Wind speeds in each event intensity level show a significant linear distribution.•High-level events are less but last longer and contribute more to wind erosion.•Sand and dust storm significantly correlates to strong wind erosion events.